Treatment of recalcitrant femur nonunion with pedicled corticoperiosteal medial femoral condyle flap - Ali Özdemir; Egemen Odabaşı; Ebubekir Eravsar; Selim Safalı; Mehmet Ali Acar (Scientific Reports, 2023)
Abstract Periosteal or osteoperiosteal medial femoral condyle (MFC) flaps may be good options for atrophic nonunion. The aim of this study was to evaluate the effectiveness and safety of pedicled MFC flap in the treatment of recalcitrant femur nonunion without bone defect. Thirteen patients (11 male and 2 female), who suffered recalcitrant femur nonunion and were treated with pedicled osteoperiosteal MFC flap between January 2014 and April 2018, were included in this study. Patient files were reviewed retrospectively. Atrophic or recalcitrant 2/3 distal femoral nonunion were the indications for this clinical procedure. Demographics and operative data, flap size, visual analog scale (VAS) score, time to union, and complications were evaluated. A total of 13 patients underwent femur nonunion treatment with MFC flap after an average of 3.4 previous surgical procedures. The median age was 34 (Q1: 32.5, Q3:43) years old. The mean flap size was 4.3 × 6.4 cm, all nonunions healed in a median 5 months (Q1: 4.5, Q3: 6). There were an intraoperative knee medial collateral ligament injury in a patient, hematoma in a patient, and seroma in two patients. The median length of the follow-up was 40 months (Q1: 30, Q3: 47). There wasn’t any additional complication in long-term follow-up. Functional outcomes were satisfactory. The median preoperative VAS score was 7 (Q1: 6, Q3: 9.5), decreasing to 1 (Q1: 0, Q3: 1) at the 6-month follow-up, and further reducing to 0 (Q1: 0, Q3: 1) at the 24-month follow-up. The nonunion period ranged from 6 to 18 months. The pedicled MFC flap is a good option for recalcitrant femur nonunion where larger vascularized flaps are not warranted. It is easy to harvest, does not require microvascular anastomosis, is effective, and offers minimal donor site morbidity.